2005
DOI: 10.4070/kcj.2005.35.7.513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Korean Carotid Intima-Media Thickness in Korean Healthy Subjects and Patients with Risk Factors: Korea Multi-Center Epidemiological Study

Abstract: Background and Objectives:We performed this study to evaluate the common carotid artery intima-media thickness (CCA IMT), and its correlation with several clinical variables, including the 10 year coronary heart disease (10 Yr CHD) risk in both healthy and hyperlipidemic hypertensive (HH) Koreans. Subjects and Methods:This was a multi-centered prospective epidemiological study. The study population consisted of 227 healthy subjects without risk factors, with the exception of age (mean 49 years old, 114 males),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
1
17
2
Order By: Relevance
“…Measurement of the CCA IMT was conducted using a computer system with automatic IMT measurement software (M'Ath ® -Std © , Metris, France). 22) The CCA IMT was measured within 2 cm proximal to the carotid bifurcation along at least 1 cm of axial length.…”
Section: Measurement Of Carotid Intima-media Thicknessmentioning
confidence: 99%
“…Measurement of the CCA IMT was conducted using a computer system with automatic IMT measurement software (M'Ath ® -Std © , Metris, France). 22) The CCA IMT was measured within 2 cm proximal to the carotid bifurcation along at least 1 cm of axial length.…”
Section: Measurement Of Carotid Intima-media Thicknessmentioning
confidence: 99%
“…In a large scale clinical study that performed carotid ultrasonography in 4,077 healthy Koreans over 27 months of a follow-up period, Cho et al 20) revealed that a low HDLc concentration was an independent risk factor for atherosclerotic stenosis of the carotid artery. In parallel, Bae et al 21) reported that a low HDLc concentration was significantly associated with increased carotid intima-media thickness, which is the important surrogate marker for CHD.…”
Section: Hdl Cholesterol and The Cardiovascular Riskmentioning
confidence: 70%
“…[1][2][3][4][5][6][7][8] Carotid IMT has also been reported to be associated with the extent or severity of CAD. [9][10][11][12] Furthermore, O'Leary et al 13) reported that an increased carotid IMT is associated with a higher risk of stroke and acute myocardial infarction(AMI) in an elderly population and it is also a more powerful predictor of cardiovascular disease than the conventional risk factors for atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%